PROGRAM PENGABDIAN KEPADA MASYARAKAT: OPTIMASI PENGGUNAAN ARTIFICIAL INTELLIGENCE DAN PENCEGAHAN ADIKSI DIGITAL - Muhammad Farras Ma’ruf; Ahmad Fauzi; Andrey Gustaph Setiawan; Defri Salsabila Oktaviani; Desi Sihamita; Luki Handoko; Risa Nur Aisiyah; Abu Khalid Rivai; Mardiyanto (Abdi Jurnal Publikasi, 2026)
The Fourth Industrial Revolution has driven digital transformation, shifting conventional automation toward interconnected intelligent systems. In this context, Generative Artificial Intelligence (Gen AI) plays a significant role across various sectors, including education, due to its ability to process diverse types of data and generate analyses rapidly. Although Gen AI has been widely adopted by the academic community, its use in learning activities requires careful supervision. A study conducted by Kosmyna et al. indicates that prolonged dependence on Gen AI for solving learning-related problems may lead to a cumulative decline in students' learning abilities. Based on these findings, a community service program was conducted at SMP Putra Pertiwi, where students are permitted to use smartphones during classroom learning activities. The program involved 12 teachers and 92 students and was implemented through two main approaches: (1) educational outreach on the potential risks of uncontrolled Gen AI usage, and (2) the design of a Gen AI–based learning system blueprint that enables schools to maintain full control over access to learning resources. The results of the program demonstrate that the educational outreach and discussions were successfully conducted with all target participants and produced a blueprint for a Gen AI–based learning system that can serve as an initial reference for schools in developing a structured, responsible, and institutionally controlled AI-supported learning environment.